CXCR7-TAGLN2 protein complex regulates invasion and metastasis in papillary thyroid carcinoma: a potential therapeutic target - Zeng, Chao; Wang, Feng; Huang, Yaomin; Zhang, Hengwei (Frontiers in Immunology, 2025)
ObjectiveTo investigate the expression and clinical significance of CXCR7 and TAGLN2 in papillary thyroid carcinoma (PTC), and to explore the molecular mechanisms underlying the interaction between CXCR7 and TAGLN2 in regulating PTC invasion and metastasis.MethodsParaffin-embedded tissue sections were obtained from 64 patients with PTC and 24 patients with nodular goiter who underwent surgical resection at The First Hospital of Lanzhou University between January 2017 and August 2020. Immunohistochemistry (IHC) was performed to assess protein expression levels of CXCR7 and TAGLN2. The associations between their expression and clinicopathological characteristics of PTC, as well as the correlation between CXCR7 and TAGLN2 expression levels, were analyzed. Human PTC cell lines were cultured in vitro, and co-immunoprecipitation (Co-IP) and immunofluorescence colocalization assays were conducted to evaluate the intracellular interaction between CXCR7 and TAGLN2. Lentiviral cotransfection techniques were employed to investigate the role of CXCR7 in modulating PTC cell invasion and metastasis via TAGLN2. Western blot analysis was performed to assess the levels of phosphorylated Smad2 (p-Smad2) and total Smad2.ResultsIHC results demonstrated that CXCR7 and TAGLN2 expression levels were significantly elevated in PTC tissues compared to benign thyroid tissues. High expression of both proteins was significantly associated with lymph node metastasis in PTC patients, and a significant positive correlation was observed between CXCR7 and TAGLN2 expression levels. In TPC-1 and BCPAP cells, CXCR7 and TAGLN2 exhibited similar subcellular localization and physically interacted. Silencing TAGLN2 markedly reduced TPC-1 and BCPAP cell migration, while concomitant overexpression of CXCR7 reversed this inhibitory effect. Mechanistically, Western blot analysis revealed that TAGLN2 knockdown led to a substantial decrease in p-Smad2 levels, confirming TAGLN2’s contribution to TGF-β signaling activation. Furthermore, re-introducing CXCR7 into TAGLN2-silenced cells restored p-Smad2 levels, demonstrating that CXCR7 actively promotes TGF-β/Smad2 signaling.ConclusionCXCR7 and TAGLN2 are overexpressed in PTC and correlate closely with lymph node metastasis. CXCR7 may regulate PTC cell migration and invasion through interaction with TAGLN2, primarily by activating the TGF-β/Smad2 signaling pathway. The CXCR7-TAGLN2 protein complex represents a potential novel therapeutic target for PTC.